2020
DOI: 10.3390/land9030084
|View full text |Cite
|
Sign up to set email alerts
|

A Synopsis of Farmland Abandonment and Its Driving Factors in Nepal

Abstract: Farmland abandonment is considered as an important phenomenon for changing eco-environmental and sociocultural landscapes of mountainous rural landscape. Many studies have analyzed farmland abandonment, its driving factors, geophysical processes and consequences at landscape: however, very few have focused on mountainous developing countries such as in Nepal, which is a rapidly urbanizing country suffering from serious farmland abandonment. Therefore, our study was an attempt to (i) assess the spatiotemporal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 109 publications
2
26
0
2
Order By: Relevance
“…Such findings align with neighbouring Kazakhstan, suggesting declining human pressure while leaving behind the decaying infrastructure (Baumann et al, 2020;Dara et al, 2020). Despite ongoing urbanization, rural hollowing is also globally widespread, for instance, in Europe (Gonz alez Ioffe et al, 2004;Quaranta et al, 2020;Westhoek et al, 2006); Northern, Central, and Southern Asia (Chaudhary et al, 2020;Liu et al, 2010;Minaei et al, 2018;Wang et al, 2016); and in the United States (Holcomb et al, 2020;USDA ERS, 2017). The abandonment of croplands can be preceded by or go hand-in-hand with the decay of rural infrastructure (Holcomb et al, 2020).…”
Section: Revealing Human-induced Disturbances With Vhr Imagesmentioning
confidence: 57%
“…Such findings align with neighbouring Kazakhstan, suggesting declining human pressure while leaving behind the decaying infrastructure (Baumann et al, 2020;Dara et al, 2020). Despite ongoing urbanization, rural hollowing is also globally widespread, for instance, in Europe (Gonz alez Ioffe et al, 2004;Quaranta et al, 2020;Westhoek et al, 2006); Northern, Central, and Southern Asia (Chaudhary et al, 2020;Liu et al, 2010;Minaei et al, 2018;Wang et al, 2016); and in the United States (Holcomb et al, 2020;USDA ERS, 2017). The abandonment of croplands can be preceded by or go hand-in-hand with the decay of rural infrastructure (Holcomb et al, 2020).…”
Section: Revealing Human-induced Disturbances With Vhr Imagesmentioning
confidence: 57%
“…During key informant interviews, respondents were worried about the fallow land due to a shortage of labour and a reduction in interest for the agriculture profession. In the Nepalese context, this view is also supported by Chaudhary et al (2020) and Shrestha et al (2019), who indicated that the majority of youth migrate within and outside the country, for employment in areas other than agriculture resulting in arable lands being left fallow. To mitigate the loss of farm labor due to migration, adequate water for irrigation should be a high priority to keep as much land as possible in vegetable production.…”
Section: Factors Influencing the Extent Of Vegetable Production Enhanced By Muws Systemmentioning
confidence: 80%
“…In the Nepalese context, farmers are smallholders and land is utilized in parcels for various purposes such as cereal production, vegetable production, agroforestry and small private forest. Due to the country's current situation of youth migration in relation to employment, lands are left fallow due to labour shortage (Chaudhary et al, 2020). It is imperative to assess factors that determine the extent of area under vegetable production.…”
Section: Model Specificationmentioning
confidence: 99%
“…Thus, the closer the service centers are, the higher the land value will be, and vice versa. Land and people are the foundations of every nation, while in urban areas, rapid economic and social development is exerting sustained pressure on land demands, and land development is essential for economic growth and the advancement of urbanization [89,90]. This condition illustrates that the existence of local communities that inhabit new urban areas will make it very difficult to engage in economic business competition, including competition for the ownership of production facilities.…”
Section: Determining Spatial Transformations In the New City Areamentioning
confidence: 99%
“…Urbanization is usually accompanied by complex challenges, including ongoing demands for housing, transportation networks, basic services, and employment [89]. These challenges seem to emphasize the economic and political dimensions of housing far more than the social and cultural dimensions [90].…”
Section: Spatial Dynamics and Environmental Quality Degradationmentioning
confidence: 99%